Laminarin Attenuates ROS-Mediated Cell Migration and Invasiveness through Mitochondrial Dysfunction in Pancreatic Cancer Cells - Woonghee Lee; Gwonhwa Song; Hyocheol Bae (MDPI AG, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a notoriously aggressive type of cancer with a high metastasis rate. It is conventionally treated by surgical resection and neoadjuvant chemotherapy. However, continuous chemotherapy leads to relapse in most PDAC patients due to chemical resistance. Therefore, novel anticancer agents need to be identified and developed. The antitumor activities of laminarin extracted from brown algae against hepatocarcinoma, lung, and colon cancer have been established. However, its effects on pancreatic cancer have remained obscure. Our study identified the anticancer effects of laminarin on pancreatic cancer cells and tried to explain its intracellular mechanisms. We assessed the cell viability of PANC-1 and MIA PaCa-2 cells using MTT assay. Hanging drop method was used for the spheroid formation. Flow cytometry was conducted to evaluate the several intracellular alterations including apoptosis, ROS production, mitochondrial membrane potential (MMP), and calcium concentration induced by laminarin. An invasion test was performed to assess the inhibitory effect of laminarin on cell migration and the invasive genes were evaluated by RT-qPCR. Signaling pathway related with anticancer effects of laminarin was analyzed by western blot. We report that inhibiting laminarin increased the proliferation and viability of the representative pancreatic cancer cell lines, MIA PaCa-2 and PANC-1. Laminarin triggered apoptosis and mitochondrial impairment as evidenced by depolarized mitochondrial membranes, disrupted calcium, and suppressed cell migration caused by reactive oxygen species production and related intracellular signaling pathways. Moreover, laminarin showed synergistic effects when combined with 5-FU, a standard anticancer agent for PDAC. The present study is the first to report that laminarin exerts anticancer effect through ROS production in pancreatic cancer cells. Laminarin shows potential to serve as a new anticancer agent for treating PDAC.